Pre-study on Potential Electrical Energy Savings in Malaysia Dairy Manufacturing Industry of Medium Enterprises. (April 2015) - Muhamad, N.A.; Phing, Lee Yun; Arief, Y.Z.
Abstract: The electrical energy consumption in dairy processing industry has been on the high side on present day. Over the years, many efforts on energy savings scheme have been carried out by government of Malaysia to highlight the sustainability of the energy supply. The study conducted at one milk manufacturing factory in Malaysia. This factory has been facing high expenses issue on electricity bill. Many professional practices have been conducted on the equipment itself but not the management of electricity consumption. The purpose of the study is to achieve energy savings for the industry through management of electricity consumption. The analysis will be focused on the industry's load profile and operations. Theoretical results show the proposed programs: lighting re-lamping, on-site generation and solar photovoltaic system can have a potential annual savings of RM 320, 603.92 and ROI is only less than 3 years. This show that implementation of management in electricity consumption can help to reduce energy in dairy industry or medium enterprise sector.